Sistem Pencatatan dan Laporan Keuangan Berbasis Web pada CV. Chalista Engineering Batam - Yandi Suprapto; Nia Enjeliana (Universitas Internasional Batam, 2021)
This study aims to design a system of accounting records and financial reports at CV Chalista Engineering Batam using a laravel framework with functions based on company needs and the appearance of this system using free templates. Methods of data collection through interviews and direct observation with business owners to find out the problems that arise in CV Chalista Engineering Batam. In this study, the company CV Chalista Engineering Batam is facing obstacles in the financial recording and reporting system, due to a lack of understanding of accounting. CV Chalista Engineering still uses a manual recording system for purchases, sales of goods, payments, and proof of cash receipts. As a result of this practical work, companies can use an accounting system developed by using a website to reduce errors in recording transactions and provide financial information for a certain period. The next PkM recommendation is to make the best use of the computerized system, especially in the accounting sector, in order to produce better financial reports than the existing ones.